Strategi Guru Menghadapi Tantangan Modernisasi Pada Pendidikan Islam Anak Usia Dini - Ridha, Nikmatur (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to analyze teachers’ strategies in addressing the challenges of modernization in Islamic early childhood education at RA Muslimat Humene. The research focuses on three main aspects: (1) the forms of modernization challenges faced by teachers in the learning process, (2) the strategies teachers employ to respond to the influence of modernization on children’s religious values, and (3) the effectiveness of these strategies in maintaining Islamic character among young children in the modern era. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and parents as the main informants. The results reveal that modernization presents challenges such as behavioral changes in children due to digital technology exposure, shifts in family values, and increasing materialistic tendencies in the social environment. Teachers at RA Muslimat Humene respond to these challenges through strategies such as role modeling (uswah hasanah), religious habituation, integrating Islamic values into the use of digital media, and active collaboration with parents. These strategies have proven effective in fostering Islamic character traits among children, such as worship independence, politeness, and social empathy. Theoretically, this study contributes to the enrichment of Islamic early childhood education studies in the context of modernization, while practically, it offers recommendations for Islamic early childhood education institutions to develop adaptive learning strategies that remain grounded in Islamic values.